2016
DOI: 10.3171/2015.12.peds15535
|View full text |Cite
|
Sign up to set email alerts
|

Transsacral transdiscal L5–S1 screws for the management of high-grade spondylolisthesis in an adolescent

Abstract: The surgical management of high-grade spondylolisthesis in adolescents remains a controversial issue. Because the basic procedure, posterolateral fusion, is associated with a significant rate of pseudarthrosis and listhesis progression, there is a pressing need for alternative surgical techniques. In the present report, the authors describe the case of an adolescent patient with significant low-back pain who was found to have Grade IV spondylolisthesis at L5–S1 that was treated with transsacral transdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…However, neurological complications are described in 25%-30% of cases. 10,15,19 In a recent review of HGS, mainly in the pediatric population, Longo et al 17 showed that there was no statistically significant difference in neurological complications in patients with reduction compared with those patients without reduction, but pseudarthrosis was more frequent in patients with in situ fixation (17.8% vs 5.5%, p = 0.004). In our series, we did not perform a reduction, as there was no sagittal imbalance in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, neurological complications are described in 25%-30% of cases. 10,15,19 In a recent review of HGS, mainly in the pediatric population, Longo et al 17 showed that there was no statistically significant difference in neurological complications in patients with reduction compared with those patients without reduction, but pseudarthrosis was more frequent in patients with in situ fixation (17.8% vs 5.5%, p = 0.004). In our series, we did not perform a reduction, as there was no sagittal imbalance in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…A total of five studies were obtained in the first search [12][13][14][15][16] , and three additional studies 9,12,17 were found in the second, including the study that proposed this technique 9 . One study was not considered because it included many patients with spondylolisthesis grades I and II 16 .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining five studies included small case series or case reports: Abdu et al 9 with three cases (the technique was described in one of them), François et al 14 with four cases and, finally, with one case report each, Beringer et al 12 , Jo et al 18 and Palejwala et al 15 . A total of 10 cases were performed in those five remaining studies.…”
Section: Figure 1 -Flow Diagram Of Our Search Mechanism According To mentioning
confidence: 99%
See 1 more Smart Citation
“…A.p. palejwala представлен случай транссакральной транспедикулярной фиксации in situ у 12-летнего подростка со спондилолистезом 4-й степени [31]. Фиксации in situ рекомендуются при сохранности параметров сагиттального баланса [32].…”
Section: Introductionunclassified